O gênero Grammostola simon, 1892: sistemática das espécies brasileiras - Borges, Leandro Malta (2023)
The genus Grammostola comprises a group of tarantula spiders that occur predominantly in the temperate zone of South America. While the genus is easily characterized and possesses a robust diagnosis, there is a significant morphological homogeneity among species, leading to taxonomic chaos and a lack of understanding regarding the true species richness. To address these systematic issues, several approaches are being employed, including the discovery of new useful morphological structures and the use of molecular markers in species delimitation. The integration of these techniques is particularly notable. In recent years, Uruguayan, Chilean, and Argentine species have received special attention, resulting in significant advances in both taxonomic knowledge and understanding general biological aspects. However, the Brazilian species have been relatively neglected, with limited in-depth studies for over 70 years. Therefore, the primary objective of this thesis is the taxonomical revision of the Brazilian species, to explore and expand the knowledge of Grammostola richness and species composition throughout the Brazilian territory. To achieve this, an integrative approach is adopted, primarily based on analyzing morphological, molecular, behavioral, and distributional data. The thesis is structured into three distinct chapters, each dedicated to delimiting and redescribing the known Brazilian species, as well as describing new species that have been identified. The findings indicate that the species richness of Grammostola in Brazil consists of six distinct species, two of which were previously unknown. Additionally, the data suggest the possible existence of cryptic species complexes, necessitating future studies to clarify these finds.